2014
DOI: 10.5951/mathteacher.108.3.0184
|View full text |Cite
|
Sign up to set email alerts
|

Probability Explorations in a Multicultural Context

Abstract: The early Hawaiian game of LuLu can be used to discuss both experimental and theoretical probability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It is interesting to note that only one cultural game was identified in this literature review. Only one study, Naresh et al (2014), identified the use of a cultural game for teaching and learning probability. The authors used a Hawaiian game called Lu-Lu for connecting experimental, theoretical and conditional probability concepts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is interesting to note that only one cultural game was identified in this literature review. Only one study, Naresh et al (2014), identified the use of a cultural game for teaching and learning probability. The authors used a Hawaiian game called Lu-Lu for connecting experimental, theoretical and conditional probability concepts.…”
Section: Discussionmentioning
confidence: 99%
“…LuLu (Naresh et al, 2014) Brief descriptions of games identified in each category and the probability constructs embedded in each game category are discussed in the two major sections below.…”
Section: Cultural Gamesmentioning
confidence: 99%
See 3 more Smart Citations